Hybrid platform for high-tech equipment protection against earthquake and microvibration. - Xu, Y. L. (Earthquake engineering & structural dynamics.)
To ensure the high quality of ultra-precision products such as semiconductors and optical microscopes, high-tech equipment used to make these products requires a normal working environment with extremely limited vibration. Some of high-tech industry centres are also located in seismic zones: the safety of high-tech equipment during an earthquake event becomes a critical issue. It is thus imperative to find an effective way to ensure the functionality of high-tech equipment against microvibration and to protect high-tech equipment from damage when earthquake events occur. This paper explores the possibility of using a hybrid platform to mitigate two types of vibration. The hybrid platform, on which high-tech equipment is installed, is designed to work as a passive isolation platform to abate mainly acceleration response of high-tech equipment during an earthquake and to function as an actively controlled platform to reduce mainly velocity response of high-tech equipment under normal working condition. To examine the performance of the hybrid platform, the analytical model of a coupled hybrid platform and building system incorporating with magnetostrictive actuators is established. The simulation results obtained by applying the analytical model to a high-tech facility indicate that the proposed hybrid platform is feasible and effective.